Strategische Planungsprozesse von Sportspieltrainerinnen und -trainern - König, S. (Spectrum der Sportwissenschaften, 2007)
Being successful in team sports requires long-term considerations, Strategie visions, and a Professional leadership - competences which the people in charge of the German Football National Team and the German Handball National Team respectively doubtlessly displayed in the forefront of and during the world championships of 2006 and 2007. From the perspective of exercise science. however, the problem is that there are hardly any concepts concerning the regulation of the collective achievements of a team which consider the complexity of the subject matter on the one hand, and focus on the responsible coaches on the other hand. Therefore, this article aims at generating various notions meant to contribute to developing a theory of successful leadership in team sports, which will be based on both an analysis of planning conceptions taken front the field of management theory and on a qualitative-quantitative research study. Final/v, the results are to provide some useful starting points for the didactical concepts of the education of coaches.